ANALISIS PERLAKUAN AKUNTANSI ATAS PEMBIAYAAN RAHN (GADAI EMAS) BERDASARKAN PSAK 407 PADA PEGADAIAN SYARIAH UPS SIMPANG MAYANG JAMBI - Nabella Laras Shati; Khairiyani; Laily Ifazah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the accounting treatment of Rahn (gold pawn financing) based on the Statement of Financial Accounting Standards (PSAK) 407 at Pegadaian Syariah UPS Simpang Mayang Jambi. The research was motivated by the decline in the number of Rahn customers during the 2022–2024 period, public misconceptions regarding the mu'nah fee, which is often perceived as interest, and the importance of implementing sharia accounting standards in accordance with PSAK 407. This research employed a descriptive qualitative approach using a case study method. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the accounting treatment of Rahn financing at Pegadaian Syariah UPS Simpang Mayang Jambi has complied with PSAK 407 regarding recognition, measurement, presentation, and disclosure. The mu'nah fee is recognized based on the appraised value of the collateral rather than the loan amount, reflecting compliance with Islamic principles that prohibit riba (interest). Presentation and disclosure are conducted through a centralized accounting information system implemented by PT Pegadaian Syariah. The main obstacles include limited technical understanding of PSAK 407 among some employees due to reliance on the automated accounting system, as well as customers' misconceptions that mu'nah represents interest. Furthermore, the decline in the number of Rahn customers was not caused by reduced public trust but rather by the company's strategy of directing customers toward other financial products such as Gold Installment Financing and Gold Savings.